Studi Density, Spektrum Energi Nukleon Dari Isotop Ca, dan Isoton N=20 dengan Model Relativistic Mean Field (RMF) - Puguh Wiyono (Politeknosains, 2019)
The property of even-even Ca isotope, and N = 20 isoione are studied within the Relativistic Mean Field lheory {RMF). To describe nucleons behaviour, in this model, the field intemctions between mesons and nucleons ere used. The proton density (pp), neutron density (o«), binding energies (Eb), two neutron or proton separation energies {S2n/S2p), potential central (Ve), surfacethickness (t«) are calculated, respectively. In this paper, we will discuss mainly the density, and the binding energy level of protons/ neutrons in the Isotope Ca-20 and Isototi N = 20